2020
DOI: 10.33546/bnj.1178
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Attitudes Toward People With Dementia Among Nursing Students in Yogyakarta, Indonesia

Abstract: Background: Nursing students are prepared to deliver care for vulnerable people, including people with dementia. Nursing students tend to have lower levels of knowledge and attitudes toward dementia compared to registered nurses. While there is less evidence that discussed this topic in the Indonesian nursing student's context, it will be necessary to identify an aspect related to knowledge and attitude among students to be considered for improvement in the future.Objective: This study aimed to identify the kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 19 publications
4
5
1
Order By: Relevance
“…This study revealed that there is still a significant correlation between knowledge level and attitudes concerning dementia ( r = 0.148, P = 0.050). Similar findings from earlier investigations have been reported [ 18 , 44 ]. This should be acknowledged that based on the knowledge-attitude-behavioral theory, knowledge could influence attitude, and attitude influence the behavior.…”
Section: Discussionsupporting
confidence: 93%
“…This study revealed that there is still a significant correlation between knowledge level and attitudes concerning dementia ( r = 0.148, P = 0.050). Similar findings from earlier investigations have been reported [ 18 , 44 ]. This should be acknowledged that based on the knowledge-attitude-behavioral theory, knowledge could influence attitude, and attitude influence the behavior.…”
Section: Discussionsupporting
confidence: 93%
“…In general, nurses' attitudes score as measured using the DAS questionnaire was 102 (Min-Max = 60-136). In line with the previous study, this attitude score is relatively high indicating that nurses have a good attitude towards PWD [18]. The statistical analysis showed that there was a positive correlation between knowledge and attitudes of nurses toward PWD (p = 0.000).…”
Section: Attitudes Of Nurses Toward Pwdsupporting
confidence: 90%
“…This questionnaire has been translated into Indonesian language. DKAS in Indonesian language has a good reliability with Cronbach's alpha = 0.674 [18]. The DKAS questionnaires used the 5 Likert Scale (1-5) with minimum score 0 and maximum score 50.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies reported that nurses had sufficient knowledge of Dementia (Balli et al, 2021;Scerri et al, 2020). However, other studies found nurses' knowledge level about Dementia is low (Chan et al, 2022;Rahmi et al, 2021;Sunaryo et al, 2020). The difference in findings from this study is from the background of the respondents involved.…”
Section: Literature Reviewcontrasting
confidence: 62%